Damage evaluation of ultra-high performance concrete columns after blast loads. Issue 1 (March 2018) - Li, Jun; Wu, Chengqing
As emerging advanced construction material, ultra-high performance concretes have seen increasing field applications over the past two decades to take advantages of their ultra-high mechanical strength and durability; yet the systematic study on its dynamic behaviour under impact and blast loads is not commonly seen. This article presents an experimental and numerical study on the static and dynamic behaviour of an existing ultra-high performance concrete material. Experimental study on its flexural behaviour under static loads is conducted and an inverse study is carried out to derive its uniaxial tensile constitutive law. The derived relationship is used in the material model in hydro-code LS-DYNA together with dynamic material properties to study ultra-high performance concrete columns under blast loads. The residual loading capacity of the column is studied and pressure–impulse diagrams for assessing the ultra-high performance concrete column damage under blast loads are proposed. Parametric study on effects of ultra-high performance concrete strength, column height, cross-section size and reinforcement ratio is performed and analytical equations are proposed for generating pressure–impulse diagrams for generic ultra-high performance concrete columns.